Oculomotor Nerve Schwannoma Associated with Acute Hydrocephalus: Case Report - IIJIMA, Keiya (Neurol Med Chir (Tokyo), 2014)
A 37-year-old woman presented with an extremely rare large oculomotor schwannoma associated with acute hydrocephalus manifesting as semicoma and anisocoria. Brain computed tomography and magnetic resonance imaging revealed a tumor in the oculomotor cistern. Cerebral angiography revealed separation of the posterior cerebral artery (PCA) and superior cerebellar artery (SCA). The tumor was removed subtotally by two stage surgery. Histological examination revealed ordinary schwannoma. The diagnosis of oculomotor nerve schwannoma was based on the intraoperative finding of the tumor origin in the oculomotor nerve. Oculomotor nerve schwannoma can cause acute hydrocephalus and manifest as impaired consciousness. The angiographical separation of the PCA and SCA was very useful for the preoperative diagnosis of oculomotor nerve schwannoma.